Modifiable Coronary Heart Disease Risk Factors in the Population Aged 20-49 Years - Francisco Carlos Valladares Mas; Francisco de Jesús Valladares Carvajal; Nicolás Ramón Cruz Pérez (Revista Finlay)
Background: evidence provided by the Framingham Heart Study established the critical role of risk factors in the development of coronary heart disease. Over half a century later, current detection and control are still inadequate. Objective: to identify modifiable risk factors of coronary heart disease in individuals aged 20 to 49 years. Methods: a descriptive, cross-sectional study was conducted in 276 individuals from the doctor’s office No. 1 of the Fabio di Celmo Community Teaching Polyclinic in Cienfuegos. Patients were examined in the clinic visit and/or whole family visit. The studied variables included age, sex, skin color, risk factors (excess weight/obesity, physical inactivity, smoking, hypertension, diabetes, dyslipidemia) and psychosocial factors, which were obtained from the medical interview, physical examination, laboratory tests (total cholesterol and triglycerides) and review of individual medical records and family history. Results: risk factors most frequently identified were excess weight/obesity (42.4 %), physical inactivity (34.4 %) and smoking (20.3 %). Presence of these risk factors increased with age, showing differences in the distribution by sex and was associated with psychosocial factors. Their coexistence and progress with age was significant. Conclusion: prevalence of modifiable risk factors for coronary heart disease in a young population was high, with frequent association, predominating factors related to unhealthy lifestyles.